Effects of a brief cognitive behavioural therapy group intervention on baseline brain perfusion in adolescents with major depressive disorder. Issue 6 (12th April 2017) - Sosic-Vasic, Zrinka; Abler, Birgit; Grön, Georg; Plener, Paul; Straub, Joana
Abstract : A number of neuroimaging studies have identified altered regional cerebral blood flow (rCBF) related to major depressive disorder (MDD) in adult samples, particularly in the lateral prefrontal, cingular and temporal regions. In contrast, neuroimaging investigations in adolescents with MDD are rare, although investigating young patients during a significant period of brain maturation might offer valuable insights into the neural mechanisms of MDD. We acquired perfusion images obtained with continuous arterial spin labelling in 21 medication-naive adolescents with MDD before and after a five-session cognitive behavioural group therapy (group CBT). A control group included medication-naive patients under treatment as usual while waiting for the psychotherapy. We found relatively increased rCBF in the right dorsolateral prefrontal cortex (DLPFC; BA 46), the right caudate nucleus and the left inferior parietal lobe (BA 40) after CBT compared with before CBT. Relatively increased rCBF in the right DLPFC postgroup CBT was confirmed by time (post vs. pre)×group (intervention/waiting list) interaction analyses. In the waiting group, relatively increased rCBF was found in the thalamus and the anterior cingulate cortex (BA 24). The relatively small number of patients included in this pilot study has to be considered. Our findings indicate that noninvasive resting perfusion scanning is suitable to identify CBT-related changes in adolescents with MDD. rCBF increase in the DLPFC following a significant reduction in MDD symptoms in adolescents might represent the core neural correlate of changes in 'top–down' cognitive processing, a possible correlate of improved self-regulation and cognitive control. Abstract : Supplemental Digital Content is available in the text.